Review of the Effect of Implant Position and Abutment Height on Removable Dentures Supported by Implants - Hadzhimuradov Burkhan Ravshanovich (Scientific Trends, 2024)
The manufacture of partial removable dentures based on implants is becoming an increasingly popular type of orthopedic treatment. Compared with non-removable dental bridges supported by implants, prosthetics using partial removable dentures supported by implants is less invasive and reduces financial costs. Tooth loss can negatively affect the aesthetics of the face, affect the functions of speech and chewing. Removable prosthetics is a common type of treatment for partial adentia. Based on the physiological, anatomical and psychological needs of the patient, diagnosis and subsequent manufacture of a denture can significantly improve the quality of life of patients and positively affect the life expectancy of the elderly population. Nevertheless, some patients are dissatisfied after the treatment and cannot use their removable dentures